Anion Guided Conformational Adjustments by Protonation Leading to Conformation Reversal. Issue 3 (9th March 2016) - Phukan, Nithi; Baruah, Jubaraj B.
Abstract: As a general outline to show anion guided conformational adjustments of an uncommon conformer found in self‐assembly of 2‐[(5‐methylthiazol‐2‐ylamino)‐methyl]‐phenol (1 ) and subsequent protonation leading to reversal of conformer is shown. On formation of nitrate salt (1 c ) the anti conformer of1 transformed to syn conformer. Whereas conformational adjustments in the corresponding syn conformer of the organocation of the chloride (1 a ) and bromide (1 b ) took place to adopt orientations that are different from the parent compound or nitrate salt. Abstract : Conformation adjustment: Uncommon anti conformer of parent compound changed to syn conformer in its nitrate salt whereas conformational adjustment took place in chloride and bromide salts.